Soil management systems on production and quality of peaches Chimarrita and Premier (Research, Society and Development, 2020)
Inappropriate soil management is one of the factors that negatively affect the productivity and quality of orchards. The objective of the work was to evaluate the interference of soil management systems in the production and quality peaches of Chimarrita and Premier varieties in two production cycles (2009/2010 and 2010/2011). The experiment was carried out with a randomized block design of five replications and six soil management systems: a) bare soil, b) spontaneous mowing plants, c) permanent mulch and managed green cover with d) herbicide, e) roller crimped and c) mowing. The production and productivity in the two productive cycles were not affected by the soil management systems. The physical-chemical characteristics of the peaches were affected in the first production cycle, being in the second only modified for the mass of fresh fruit and pulp firmness. The mulch treatment provided greater fresh weight of the fruit (130.4 g) in the Chimarrita variety and the use of spontaneous brushing with less firmness of the pulp (10.3 N) for the Premier variety. Short-term soil management systems influenced only the fresh fruit mass and pulp firmness.